The Effect of The Length Thawing Time of Bali Cattle’s Frozen Semen Produced By UPT BIBD Baturiti at Quality Test Before Distribution - N. L. A., Adnyani; Sumardani, N. L. G.; Sarini, N. P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
Frozen semen quality test before distribution was very important.  The purpose of this study was to find out the effect of the length thawing time of bali cattle’s frozen semen produced by UPT BIBD Baturiti at quality test before distribution.  This study was carried out at UPT BIBD Baturiti Laboratory, Baturiti village, Baturiti district, Tabanan Regencyfor four weeks.  It was designed using Completely Randomized Design (CRD) with 4 treatments and 3 repetitions hence there was 12 experimental units.  Those treatments were 4 thawing times, which were 15 second (A), 30 second (B), 45 second (C) and 60 second (D).  Variable observered were sperm motility, sperm concentration, life sperm percentage and sperm abnormality.  The result showed that the length thawing time gave very significant effect (P<0,01) to sperm motility and significant effect (P<0,05) to life sperm percentage. On the contrary to sperm concentration and sperm abnormality.  Therefore it can be concluded that the best quality of frozen semen of bali catlle that was thawed for 30 seconds in 37ºC temperature.  Meanwhilethawing for 45 seconds was abled to maintain the quality fozen semen bali catlle.   Keywords: thawing, test quality, frozen semen, bali cattle’s.